Longitudinal influence of self-compassion and fears of compassion on prosocial and antisocial behaviour in sport: A conditional latent growth curve modelling analysis - McEwan, K.; Zhang, S. (International Journal of Sport and Exercise Psychology, 2024)
The impact of self-compassion on athlete wellbeing is well established. Much less researched is the impact of self-compassion, and its related fears (hereafter "fears of compassion") on athletes` prosocial and antisocial behaviours. Indeed, sporting contexts offer opportunities for athletes to demonstrate prosocial and antisocial behaviours towards teammates and competitors, and these behaviours could lead to various performance and wellbeing-related consequences. Given the well-documented benefits of a compassion, and the intention to investigate alternative antecedents or predictors of prosocial and antisocial behaviour in sport, we assessed the longitudinal influences of self-compassion and fears of compassion on athletes` prosocial and antisocial behaviours. The study used a repeated measures design, where 324 athletes (174 male, 150 female) from 35 different sports (22 individual sports, 13 team sports) completed surveys at baseline and the 4th and 8th month. Conditional latent growth curve modelling revealed higher self-compassion and lower fears of receiving compassion from others at baseline were associated with greater prosocial behaviours, whilst higher fears of self-compassion were associated with higher antisocial behaviour, over eight months. Results also revealed a trend for antisocial behaviour to increase across the study period. Compassion-based interventions may be of value to athletes to improve prosocial behaviours in sport contexts.